(untitled) (Interdisciplinary Studies Journal, 2021)
This article presents an analysis that combined four data collection instruments to explore different narratives related to intangible aspects of the industrial heritage of the Federal University of Pelotas (UFPel). The built heritage of this university comprises various examples representative of the different socio-economic contexts experienced by the city, among which the remnants of Pelotas’ industrial heritage are the most recently incorporated. UFPel has material and immaterial resources to enhance the value of this cultural heritage through increasingly accessible actions that encourage community participation. This essay is part of a research project that aims to understand intangible aspects contained in the memories, perceptions, attributed values, and emotional ties between former workers and their old workplaces. Their narratives can be assimilated as "a great counsel" in this process of knowledge construction, contributing to filling existing gaps both in the population’s sense of ownership regarding this heritage and in safeguarding practices related to it.